Application of zirconium pyrophosphate as coating dopant, positive electrode material, preparation method and battery

By using zirconium pyrophosphate as the coating dopant, the doping and coating process of nickel-manganate material is simplified, and the problem of poor circulation performance of nickel-manganate material is solved, achieving the effect of improving battery performance and reducing costs.

CN119965275APending Publication Date: 2025-05-09SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510171363.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

During the charging and discharging process, the surface lattice oxygen release of nickel-manganate material leads to structural changes, which leads to poor cycling performance of the battery, and the traditional doping and coating processes are complex and costly.

Method used

Zirconium pyrophosphate is used as the coating dopant, and the doping and coating of the nickel-manganese hydroxide precursor and the lithium source are mixed with the nickel-manganese lithium hydroxide material is achieved, simplifying the process flow and reducing costs.

Benefits of technology

Effectively inhibit the surface lattice oxygen release of the nickel-manganate lithium material during charging and discharging, improve the cycling performance of the battery, and reduce the preparation cost and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119965275A_ABST
    Figure CN119965275A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to application of zirconium pyrophosphate as a positive electrode material coating dopant, a positive electrode material, a preparation method and a battery, and the positive electrode material is lithium nickel manganese oxide; mixing the zirconium pyrophosphate with a nickel manganese hydroxide precursor and a lithium source, and performing primary sintering treatment to obtain a positive electrode material; the positive electrode material comprises a core part and a coating layer. Zirconium pyrophosphate is adopted as a positive electrode material coating doping agent, meanwhile, lithium nickel manganese oxide is doped and coated, Zr < 4 + > and O can form a strong Zr-O bond, surface lattice oxygen release of the lithium nickel manganese oxide material in the charging and discharging process is effectively inhibited, meanwhile, a Li3PO4 fast ion conductor coating layer is formed on the surface of the lithium nickel manganese oxide, on one hand, on the other hand, the surface of the lithium nickel manganese oxide material is effectively protected, and on the other hand, the surface of the lithium nickel manganese oxide material is protected; on the other hand, the coating layer has good ion transmission capability, so that the influence on lithium ion transmission caused by coating can be effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to the application of zirconium pyrophosphate as a coating dopant, a positive electrode material and a preparation method, and a battery. Background Art

[0002] Lithium Nickel Manganese Oxide (LiNi 0.5 Mn 1.5 O4) as a high voltage cathode material with a high voltage of 4.7V (vs. Li / Li + ) discharge platform, with a specific energy of more than 600Wh / kg and without cobalt, it is more environmentally friendly and relatively inexpensive, making it one of the most promising next-generation high-voltage positive electrode materials for commercialization.

[0003] However, the surface lattice oxygen release of lithium nickel manganese oxide materials during the charging and discharging process causes structural changes, which in turn leads to poor battery cycle performance.

[0004] In traditional technology, lithium nickel manganese oxide materials are modified by doping and coating, but doping and coating need to be carried out in batches, the process is relatively complicated and the cost is high. Summary of the invention

[0005] Based on this, it is necessary to provide an application of zirconium pyrophosphate as a coating dopant, a positive electrode material and a preparation method, and a battery, in which the doping and coating of the lithium nickel manganese oxide material are completed in one step, shortening the process flow, ensuring the conductive properties of the positive electrode material, reducing costs, and improving the cycle performance of the battery.

[0006] The first aspect of the present application provides the use of zirconium pyrophosphate as a coating dopant, wherein zirconium pyrophosphate is mixed with a nickel manganese hydroxide precursor and a lithium source and then subjected to a sintering treatment to obtain a positive electrode material; the positive electrode material includes a core and a coating layer.

[0007] In some embodiments, the coating layer has a thickness of 2 nm to 5 nm.

[0008] In some embodiments, the coverage of the coating layer is greater than 85%.

[0009] In some embodiments, the core portion has the general formula Li a Ni b Mn (8-a-4b-4x) Zr x O4,0 <a<1;0<b<1;0<x<1.5。

[0010] The second aspect of the present application provides a method for preparing a positive electrode material, which includes using zirconium pyrophosphate as a coating dopant. The positive electrode material is prepared by the following steps: zirconium pyrophosphate, a nickel manganese hydroxide precursor, and a lithium source are mixed and sintered to obtain the positive electrode material.

[0011] In some embodiments, the sintering temperature is 900°C to 950°C.

[0012] In some embodiments, the particle size ratio of the nickel manganese hydroxide precursor to the zirconium pyrophosphate is (100:1) to (500:1).

[0013] In some embodiments, the particle size of the nickel manganese hydroxide precursor is 5 μm to 10 μm.

[0014] In some embodiments, the particle size of zirconium pyrophosphate is 20 nm to 50 nm.

[0015] In some embodiments, the mass ratio of the nickel manganese hydroxide precursor to the zirconium pyrophosphate is 1:(0.005-0.01).

[0016] The third aspect of the present application provides a positive electrode material, which is prepared by using zirconium pyrophosphate as a coating dopant.

[0017] A fourth aspect of the present application provides a battery, which includes the positive electrode material provided by the third aspect.

[0018] Compared with the traditional technology, this application has at least the following beneficial effects:

[0019] First, the present application uses zirconium pyrophosphate as a dopant for coating the positive electrode material, and simultaneously dopes and coats the lithium nickel manganese oxide. Compared with the traditional lithium nickel manganese oxide modification in which doping and coating need to be carried out step by step, the process flow is greatly simplified, and preparation time and cost are saved.

[0020] Secondly, when zirconium pyrophosphate is used as a dopant coating for the positive electrode material, Zr 4+ It can form a strong Zr-O bond with O, effectively inhibiting the release of oxygen from the surface lattice of the lithium nickel manganese oxide material during the charging and discharging process, and at the same time forming a Li3PO4 fast ion conductor coating on the surface of the lithium nickel manganese oxide. On the one hand, it can effectively isolate the contact between the core and the electrolyte. On the other hand, the coating has good ion transmission ability, which can effectively avoid the influence of lithium ion transmission caused by the coating.

[0021] The preparation method of the positive electrode material provided in the present application is to mix zirconium pyrophosphate, a nickel manganese hydroxide precursor and a lithium source and then sinter them, so that the nickel manganese hydroxide precursor is converted into lithium nickel manganese oxide, and the pyrophosphate ions in the zirconium pyrophosphate will undergo bond breaking and decomposition at high temperature to form phosphate ions. Due to the reaction kinetics, the phosphate ions migrate to the outer layer and combine with the lithium ions in the lithium source to form a thin, uniform and continuous Li3PO4 fast ion conductor coating on the surface of the lithium nickel manganese oxide, which can effectively reduce the problem of energy density reduction caused by coating, which is beneficial to shorten the transmission distance of lithium ions, increase the transmission speed of lithium ions, and improve the fast charging performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A cross-sectional SEM test image of the positive electrode material in Example 1 of the present application is provided.

[0023] Figure 2 A surface TEM test image of the positive electrode material in Example 1 of the present application is provided.

[0024] Figure 3 A cross-sectional EDS-Zr test image of the positive electrode material in Example 1 of the present application is provided.

[0025] Figure 4 A surface EDS-P test image of the positive electrode material in Example 1 of the present application is provided.

[0026] Figure 5 A surface SEM test image of the positive electrode material in Comparative Example 1 of the present application is provided. DETAILED DESCRIPTION

[0027] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0028] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0030] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0035] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0036] The first aspect of the present application provides the application of zirconium pyrophosphate as a coating dopant, specifically as a coating dopant for a positive electrode material. Zirconium pyrophosphate is mixed with a nickel manganese hydroxide precursor and a lithium source and then subjected to a sintering treatment to obtain a positive electrode material; the positive electrode material includes a core and a coating layer.

[0037] First, the present application uses zirconium pyrophosphate as a dopant for coating the positive electrode material, and simultaneously achieves doping and coating of lithium nickel manganese oxide. Compared with the traditional lithium nickel manganese oxide modification in which doping and coating need to be carried out step by step, the process flow is greatly simplified, saving preparation time and cost.

[0038] Secondly, when zirconium pyrophosphate is used as a dopant coating for the positive electrode material, Zr 4+ It can form a strong Zr-O bond with O, effectively inhibiting the release of oxygen from the surface lattice of the lithium nickel manganese oxide material during the charging and discharging process, and at the same time forming a Li3PO4 fast ion conductor coating on the surface of the lithium nickel manganese oxide. On the one hand, it can effectively isolate the contact between the core and the electrolyte. On the other hand, the coating has good ion transmission ability, which can effectively avoid the influence of lithium ion transmission caused by the coating.

[0039] In some embodiments, the coating layer has a thickness of 2 nm to 5 nm. For example, the coating layer has a thickness of 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, and 5 nm.

[0040] The coating layer is relatively thin, which can effectively reduce the problem of energy density decrease caused by coating, which is beneficial to shorten the transmission distance of lithium ions, increase the transmission speed of lithium ions, and improve the fast charging performance of the battery.

[0041] In some embodiments, the coating layer continuously coats the surface of the core portion.

[0042] In some embodiments, the coverage of the coating layer is greater than 85%. It is understood that the coverage here is calculated by selecting several regions in the SEM image and calculating the ratio of the area of ​​the region containing the coating layer to the total area of ​​the region.

[0043] In some embodiments, the core portion has the general formula Li a Ni b Mn (8-a-4b-4x) Zr x O4,0 <a<1;0<b<1;0<x<1.5。

[0044] In some embodiments, the coating layer includes lithium phosphate.

[0045] The second aspect of the present application provides a method for preparing a positive electrode material, the method comprising using zirconium pyrophosphate as a coating dopant and preparing the material by the following steps:

[0046] Zirconium pyrophosphate, a nickel manganese hydroxide precursor and a lithium source are mixed and sintered to obtain a positive electrode material.

[0047] It is understandable that, unlike phosphate ions, pyrophosphate ions will undergo bond breaking and decomposition at high temperatures to form phosphate ions. Due to the reaction kinetics, phosphate ions migrate to the outer layer and interact with Li + The reaction forms a Li3PO4 coating layer, and the Zr in zirconium pyrophosphate 4+ It will migrate to the center of the lithium nickel manganese oxide crystal structure and bond with O to form doping.

[0048] The preparation method provided by the present application can obtain the positive electrode material by sintering only once, and the doping and coating of the lithium nickel manganese oxide material are completed in one step, which shortens the process flow and greatly reduces the cost. Moreover, unlike the coating layer prepared by the traditional two-step method, the traditional coating layer is characterized by the coating material being discretely attached to the surface of the core material in the form of particles. The coating layer prepared by the present method has a large amount of phosphate ions and Li on the surface of the core. + The coating layer is recombined to form a continuous coating layer with a thin thickness.

[0049] In some embodiments, the temperature of the sintering process is 900° C. to 950° C. For example, the temperature of the sintering process includes but is not limited to 900° C., 910° C., 920° C., 930° C., 940° C., and 950° C.

[0050] In some embodiments, the mass ratio of the nickel manganese hydroxide precursor to the zirconium pyrophosphate is 1:(0.005-0.01). Exemplarily, the mass ratio of the nickel manganese hydroxide precursor to the zirconium pyrophosphate includes but is not limited to 1:0.005, 1:0.006, 1:0.007, 1:0.008, 1:0.009, and 1:0.01.

[0051] In some embodiments, the particle size ratio of the nickel manganese hydroxide precursor to the zirconium pyrophosphate is (100:1) to (500:1). Exemplarily, the particle size ratio of the nickel manganese hydroxide precursor to the zirconium pyrophosphate includes but is not limited to 100:1, 200:1, 300:1, 400:1, and 500:1.

[0052] In some embodiments, the particle size of the nickel manganese hydroxide precursor is 5 μm to 10 μm. For example, the particle size of the nickel manganese hydroxide precursor includes but is not limited to 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.

[0053] In some embodiments, the particle size of zirconium pyrophosphate is 20nm to 50nm. Exemplarily, the particle size of zirconium pyrophosphate includes but is not limited to 20nm, 30nm, 40nm, and 50nm. Controlling the particle size of zirconium pyrophosphate within the above range is conducive to the melting of zirconium pyrophosphate, which is conducive to the bond breaking and decomposition of pyrophosphate ions in zirconium pyrophosphate to form phosphate ions, thereby generating a coating layer.

[0054] In some embodiments, the sintering time is 10 h to 20 h. Exemplarily, the sintering time includes but is not limited to 10 h, 12 h, 14 h, 16 h, 18 h, and 20 h.

[0055] In some embodiments, the lithium source is selected from one or more of lithium hydroxide and lithium carbonate.

[0056] In some embodiments, after the nickel manganese hydroxide precursor, zirconium pyrophosphate and lithium source are mixed and sintered to obtain the positive electrode material, the method for preparing the positive electrode material further includes: preparing the nickel manganese hydroxide precursor.

[0057] In some embodiments, preparing a nickel manganese hydroxide precursor specifically comprises the following steps:

[0058] S1. prepare a mixed solution of manganese salt / nickel salt, an aqueous ammonia solution and a sodium hydroxide solution.

[0059] Among them, the molar ratio of manganese salt to nickel salt is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 0.1mol / L~2mol / L, the molar concentration of ammonia solution is 2mol / L~5mol / L, and the molar concentration of sodium hydroxide solution is 2mol / L~5mol / L.

[0060] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into the reaction kettle through a peristaltic pump for reaction and aging.

[0061] The reaction temperature is 50°C~70°C, the pH of the reaction solution is 8~10.5, the reaction is carried out under a nitrogen atmosphere, and the aging time is 10h~15h.

[0062] S3, centrifuging, washing and drying the aged slurry to obtain a nickel manganese hydroxide precursor.

[0063] In some embodiments, the particle size of the nickel manganese hydroxide precursor is controlled by controlling the reaction time.

[0064] In some embodiments, the nickel salt is selected from one or more of nickel sulfate, nickel nitrate and nickel halide.

[0065] In some embodiments, the manganese salt is selected from one or more of manganese sulfate, manganese nitrate and manganese halide.

[0066] The third aspect of the present application provides a positive electrode material, which is prepared by using zirconium pyrophosphate as a coating dopant.

[0067] A fourth aspect of the present application provides a battery, which includes the positive electrode material provided by the third aspect.

[0068] In some embodiments, the battery includes a positive electrode plate, and the positive electrode plate includes the positive electrode material provided in the third aspect.

[0069] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on a surface of the positive electrode current collector.

[0070] In some embodiments, the positive electrode material accounts for 78% to 99% of the positive electrode material layer by mass. Further, the positive electrode material accounts for 90% to 99% of the positive electrode material layer by mass.

[0071] In some embodiments, the positive electrode current collector is selected from metal foil and composite current collector; the composite current collector has a sandwich structure similar to a sandwich, the middle polymer layer is mainly a polymer insulating resin and other materials, and the metal layer is deposited on both sides of the middle polymer layer by electroplating, chemical plating or other methods. Schematically, the polymer resin includes polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyimide, polyamide, polyethylene glycol, polyamide-imide, polycarbonate, cyclopentane One or more of polyolefin, polyphenylene sulfide, polyvinyl acetate, polytetrafluoroethylene, polymethylene naphthalene, polyvinylidene fluoride, polyethylene naphthalate, polypropylene carbonate, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene), silicone, vinylon, polypropylene, polyethylene, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyphenylene ether, polyester, polysulfone and its derivatives, sodium carboxymethyl cellulose, styrene-butadiene rubber, fluorinated rubber, polyvinyl alcohol or polyvinylidene fluoride. The material of the metal layer is selected from at least one of aluminum, copper, nickel, cobalt, tungsten, tin, lead, iron, silver or gold. Further, the positive electrode current collector is aluminum foil.

[0072] In some embodiments, the positive electrode material layer also includes a conductive agent, which plays a role in collecting microcurrent between the positive electrode materials and between the positive electrode material and the positive electrode current collector.

[0073] In some embodiments, the conductive agent accounts for 1% to 10% by mass in the positive electrode material layer.

[0074] In some of the embodiments, the conductive agent includes graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, super-P and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the aspect of improving conductivity, the conductive agent may preferably be super-P.

[0075] In some embodiments, the specific surface area of ​​the conductive agent can be 80 m 2 / g~200 m 2 / g, preferably 100m 2 / g~150 m 2 / g.

[0076] In some of the embodiments, the positive electrode material layer further includes a binder, which can serve to bind the positive electrode material and the conductive agent together; the binder accounts for 1% to 10% of the mass of the positive electrode material layer.

[0077] In some embodiments, the binder includes a fiberizable binder. It is understood that the fiberizable binder means that the binder can be transformed from a granular state to a fiber state under a high shear force.

[0078] In some embodiments, the fiberizable binder is selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene (PE), and polypropylene (PP). Further, the fiberizable binder is selected from at least one of polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).

[0079] In some of the embodiments, in order to further enhance the bonding effect of the positive electrode system, the positive electrode material layer also includes a second binder; the second binder is selected from at least one of polyvinylidene fluoride, polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose (CMC), polyvinyl pyrrolidone (HPC), polyethylene (PE), polypropylene (PP), ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), and fluororubber (FKM).

[0080] In some of the embodiments, the positive electrode material layer further comprises solid electrolyte powder for improving the ionic conductivity of the composite positive electrode. The present invention does not limit the type of solid electrolyte powder.

[0081] In some embodiments, the solid electrolyte powder is selected from at least one of oxide solid electrolyte powder, sulfide solid electrolyte powder and halide solid electrolyte powder; further, the solid electrolyte powder is selected from halide solid electrolyte powder.

[0082] In some embodiments, the mass percentage of the solid electrolyte powder in the positive electrode material layer is 1% to 18%; further, the mass percentage of the solid electrolyte powder in the positive electrode material layer is 5% to 18%.

[0083] In some embodiments, the thickness of the positive electrode material layer may be 30 μm to 400 μm, for example, 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50 μm to 110 μm.

[0084] In some embodiments, the battery also includes an electrolyte, and the electrolyte includes a solvent and an electrolyte salt. The solvent includes at least one of an ether solvent, propylene carbonate and fluoroethylene carbonate. The electrolyte salt can be lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalate borate) (LiBOB), lithium bis(oxalate borate) (LiODFB), lithium difluorobis(oxalate phosphate) (LiODFP) or lithium tetrafluorooxalate phosphate (LiTFOP).

[0085] In some embodiments, based on the total mass of the electrolyte being 100%, the mass percentage of the electrolyte salt is 0.5% to 25%.

[0086] In some embodiments, the electrolyte further comprises an additive, wherein the additive comprises at least one of 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 4-methyl vinyl sulfate, propenyl sulfate, saturated phosphate compounds and unsaturated phosphate compounds, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, tris(triethylsilane) borate, succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid nitrile, and sebaconitrile.

[0087] In some embodiments, the battery further comprises a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode material layer formed on the surface of the negative electrode current collector, wherein the negative electrode material layer comprises at least a negative electrode material and a binder.

[0088] In some of the embodiments, the negative electrode material in the embodiments of the present application is not particularly limited, as long as it is a material that can electrochemically absorb and release S-zone metal ions such as lithium ions, sodium ions, potassium ions, magnesium ions, etc., such as carbonaceous materials, metal compound materials, or their oxides, carbides, nitrides, silicides, sulfides, phosphides, etc. These substances can be used alone, or two or more can be used in combination.

[0089] In some of the embodiments, a carbon material can be selected as the negative electrode material, and specifically one or more of the following can be selected: graphite, needle coke, amorphous carbon, a carbon-containing mesophase, carbon fiber, and a carbon material with a low degree of graphitization. Among them, graphite can include natural graphite, artificial graphite, and the like. In addition, materials obtained by coating them with carbon materials, such as amorphous carbon and graphitized materials, can also be used. Amorphous carbon includes, but is not limited to, particles obtained by firing the entire mesophase, and particles obtained by infusible treatment and firing of a carbon precursor. As carbonaceous particles with a low degree of graphitization, particles obtained by firing organic matter at a temperature generally below 2500°C can be cited.

[0090] In some embodiments, the non-metallic materials that can be used as negative electrode materials also include silicon and its compounds, such as Si, SiO x (0≤x<2), since silicon-containing materials are prone to expansion, easy to fall off from the negative electrode current collector, and have poor conductivity, they are often mixed with carbon materials, such as a core-shell structure containing a carbon coating layer.

[0091] In some of the embodiments, metal elements and metal compounds can also be selected as negative electrode materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.

[0092] In some embodiments, the mass percentage of the negative electrode material contained in the negative electrode material layer can be 80% to 99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.

[0093] In some embodiments, when the negative electrode material is a non-metallic material such as a carbon material, the binder may be an aqueous binder such as one or more of sodium hydroxymethyl cellulose, styrene-butadiene latex, polyacrylic acid, acrylic copolymer, cyclodextrin, and the like.

[0094] In some embodiments, the negative electrode material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode material and a binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.

[0095] In some embodiments, the thickener in the examples of the present application can be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein and their salts, etc.

[0096] In some embodiments, the mass proportion of the thickener in the negative electrode slurry can be 0.1%~5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%~3%, and more preferably 0.6%~2%.

[0097] In some embodiments, the battery provided in the fourth aspect is used to provide power for electrical devices.

[0098] The electrical device of the present application is not particularly limited, and it can be any electrical device known in the prior art. For example, the electrical device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0099] The present application will be further described below with reference to specific embodiments and comparative examples.

[0100] Example 1

[0101] The present embodiment provides an application of zirconium pyrophosphate as a coating dopant, a positive electrode material and a preparation method thereof, a positive electrode plate, and a battery.

[0102] Application of zirconium pyrophosphate as coating dopant and preparation method of positive electrode material:

[0103] (1) Preparation of nickel manganese hydroxide precursor Ni 0.25 Mn 0.75 (OH)2:

[0104] S1. Prepare a mixed solution of manganese salt / nickel salt, an ammonia solution and a sodium hydroxide solution with deionized water.

[0105] The molar ratio of manganese salt manganese nitrate to nickel salt nickel nitrate is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 1.5 mol / L, the molar concentration of ammonia water is 2 mol / L; and the molar concentration of sodium hydroxide is 5 mol / L.

[0106] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into a reaction kettle through a peristaltic pump for reaction and aging.

[0107] The reaction temperature was 55°C, the pH of the reaction solution was 10.2, and nitrogen protection was introduced throughout the process.

[0108] S3, centrifuge, wash and dry the aged slurry to obtain Ni 0.25 Mn 0.75 (OH)2.

[0109] (2) Preparation of positive electrode material: The above Ni 0.25 Mn 0.75 (OH)2, the coating dopant zirconium pyrophosphate and the lithium source lithium hydroxide are mixed in a mass ratio of 1:0.016:0.238 and then sintered to obtain a positive electrode material.

[0110] The sintering temperature is 920℃, the sintering time is 10h, and Ni 0.25 Mn 0.75 The particle size of (OH)2 is 6 μm, the particle size of zirconium pyrophosphate is 20 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2 and zirconium pyrophosphate is 300:1.

[0111] The total time used for the preparation of the positive electrode material is 18 h.

[0112] Cathode Material:

[0113] The positive electrode material is prepared by the above-mentioned preparation method, and the positive electrode material includes a core part and a coating layer, and the coating layer is coated on at least a part of the surface of the core part. The core part includes Li 0.5 Ni 0.5 Mn 1.47 Zr 0.03 O4, the coating layer includes Li3PO4, the thickness of the coating layer is 4.6nm, and the coverage is 95%.

[0114] like Figures 1 to 4 As shown, the positive electrode material provided in this embodiment is a spinel structured lithium nickel manganese oxide material doped with Zr ions, and a Li3PO4 coating layer is formed on the surface.

[0115] Positive electrode:

[0116] The positive electrode material, conductive agent Super-P and binder PVDF are weighed according to a mass ratio of 90:5:5, mixed to obtain a slurry, coated on an aluminum foil to form a positive electrode material layer, and dried and rolled to obtain a positive electrode sheet.

[0117] Battery:

[0118] The positive electrode sheet, negative electrode sheet and separator prepared above are stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.

[0119] Among them, the negative electrode plate includes negative electrode material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.

[0120] Example 2

[0121] The application of zirconium pyrophosphate as a coating dopant, the preparation method of the positive electrode material, the positive electrode material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Example 1, except that:

[0122] Application of zirconium pyrophosphate as coating dopant and preparation method of positive electrode material:

[0123] In step (2), Ni 0.25 Mn 0.75 The mass ratio of (OH)2 and zirconium pyrophosphate is 1:0.006.

[0124] Cathode Material:

[0125] The thickness of the coating layer is 2.2 nm and the coverage of the coating layer is 90%.

[0126] Example 3

[0127] The application of zirconium pyrophosphate as a coating dopant, the preparation method of the positive electrode material, the positive electrode material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Example 1, except that:

[0128] Preparation method of positive electrode material:

[0129] In step (2), Ni 0.25 Mn 0.75 The mass ratio of (OH)2 and zirconium pyrophosphate is 1:0.01.

[0130] Cathode Material:

[0131] The thickness of the coating layer is 3.5 nm and the coverage of the coating layer is 98%.

[0132] Example 4

[0133] The application of zirconium pyrophosphate as a coating dopant, the preparation method of the positive electrode material, the positive electrode material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Example 1, except that:

[0134] Preparation method of positive electrode material:

[0135] In step (2), Ni 0.25 Mn 0.75 The particle size of (OH)2 is 5 μm, the particle size of zirconium pyrophosphate is 50 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2 and zirconium pyrophosphate is 100:1.

[0136] Cathode Material:

[0137] The thickness of the coating layer is 2.6 nm and the coverage of the coating layer is 92%.

[0138] Example 5

[0139] The application of zirconium pyrophosphate as a coating dopant, the preparation method of the positive electrode material, the positive electrode material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Example 1, except that:

[0140] Preparation method of positive electrode material:

[0141] In step (2), Ni 0.25 Mn 0.75 The particle size of (OH)2 is 10 μm, the particle size of zirconium pyrophosphate is 20 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2 and zirconium pyrophosphate is 500:1.

[0142] Cathode Material:

[0143] The thickness of the coating layer is 3.2 nm and the coverage of the coating layer is 97%.

[0144] Example 6

[0145] The application of zirconium pyrophosphate as a coating dopant, the preparation method of the positive electrode material, the positive electrode material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Example 1, except that:

[0146] Preparation method of positive electrode material:

[0147] In step (2), the sintering temperature is 900°C.

[0148] The total time used for the preparation of the positive electrode material was 17.4 h.

[0149] Cathode Material:

[0150] The thickness of the coating layer is 2.8 nm and the coverage of the coating layer is 91%.

[0151] Example 7

[0152] The application of zirconium pyrophosphate as a coating dopant, the preparation method of the positive electrode material, the positive electrode material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Example 1, except that:

[0153] Preparation method of positive electrode material:

[0154] In step (2), the sintering temperature is 950°C.

[0155] The total time used for the preparation of the positive electrode material was 18.6 h.

[0156] Cathode Material:

[0157] The thickness of the coating layer is 3.1 nm and the coverage of the coating layer is 96%.

[0158] Comparative Example 1

[0159] This comparative example provides a method for preparing a positive electrode material, a positive electrode material, a positive electrode plate, and a battery, without using zirconium pyrophosphate as a coating dopant.

[0160] Preparation method of positive electrode material:

[0161] (1) Preparation of nickel manganese hydroxide precursor Ni 0.25 Mn 0.75 (OH)2:

[0162] S1. Prepare a mixed solution of manganese salt / nickel salt, an ammonia solution and a sodium hydroxide solution with deionized water.

[0163] The molar ratio of manganese salt manganese nitrate to nickel salt nickel nitrate is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 1.5 mol / L, the molar concentration of ammonia water is 2 mol / L; and the molar concentration of sodium hydroxide is 5 mol / L.

[0164] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into a reaction kettle through a peristaltic pump for reaction and aging.

[0165] The reaction temperature was 55°C, the pH of the reaction solution was 10.2, and nitrogen protection was introduced throughout the process.

[0166] S3, centrifuge, wash and dry the aged slurry to obtain Ni 0.25 Mn 0.75 (OH)2.

[0167] (2) Preparation of positive electrode materials:

[0168] The above Ni 0.25 Mn 0.75 (OH)2, dopant ZrO2 and lithium source lithium hydroxide are mixed in a mass ratio of 1:0.008:0.238 and then sintered once to obtain an intermediate; then the intermediate and coating agent NH4H2PO4 are sintered twice in a mass ratio of 1:0.008 to obtain a positive electrode material.

[0169] The primary sintering temperature is 750℃, the primary sintering time is 10 h, and the Ni 0.25 Mn 0.75 The particle size of (OH)2 is 6 μm, the particle size of ZrO2 is 20 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2 and zirconium pyrophosphate is 300:1, the temperature of the secondary sintering treatment is 550 ℃, and the time of the secondary sintering treatment is 12 h.

[0170] The total time used for the preparation of the positive electrode material is 30 h.

[0171] Cathode Material:

[0172] The positive electrode material is prepared by the above preparation method, such as Figure 5 As shown, the positive electrode material includes a core and a coating layer, and the coating layer covers at least a portion of the surface of the core. The core includes Li 0.5 Ni 0.5 Mn 1.47 Zr 0.03 O4, the coating layer includes Li3PO4, the thickness of the coating layer is 40nm, and the coverage is 63%.

[0173] Positive electrode:

[0174] The positive electrode material, conductive agent Super-P and binder PVDF are weighed according to a mass ratio of 90:5:5, mixed to obtain a slurry, coated on an aluminum foil to form a positive electrode material layer, and dried and rolled to obtain a positive electrode sheet.

[0175] Battery:

[0176] The positive electrode sheet, negative electrode sheet and separator prepared above are stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.

[0177] Among them, the negative electrode plate includes negative electrode material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.

[0178] Comparative Example 2

[0179] This comparative example provides a method for preparing a positive electrode material, a positive electrode material, a positive electrode plate, and a battery.

[0180] Preparation method of positive electrode material:

[0181] (1) Preparation of nickel manganese hydroxide precursor Ni 0.25 Mn 0.75 (OH)2:

[0182] S1. Prepare a mixed solution of manganese salt / nickel salt, an ammonia solution and a sodium hydroxide solution with deionized water.

[0183] The molar ratio of manganese salt manganese nitrate to nickel salt nickel nitrate is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 1.5 mol / L, the molar concentration of ammonia water is 2 mol / L; and the molar concentration of sodium hydroxide is 5 mol / L.

[0184] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into a reaction kettle through a peristaltic pump for reaction and aging.

[0185] The reaction temperature was 55°C, the pH of the reaction solution was 10.2, and nitrogen protection was introduced throughout the process.

[0186] S3, centrifuge, wash and dry the aged slurry to obtain Ni 0.25 Mn 0.75 (OH)2.

[0187] (2) Preparation of positive electrode material: The above Ni 0.25 Mn 0.75 (OH)2, zirconium phosphate and lithium hydroxide, a lithium source, are mixed in a mass ratio of 1:0.008:0.238 and then sintered to obtain a positive electrode material.

[0188] The sintering temperature is 920℃, the sintering time is 10h, and Ni 0.25 Mn 0.75 The particle size of (OH)2 is 6 μm, the particle size of zirconium phosphate is 20 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2 and zirconium phosphate is 300:1.

[0189] The total time used for the preparation of the positive electrode material is 18 h.

[0190] Cathode Material:

[0191] The positive electrode material is prepared by the above preparation method, and the positive electrode material includes Li 0.5 Ni 0.5 Mn 1.47 Zr 0.03 O4.

[0192] Positive electrode:

[0193] The positive electrode material, conductive agent Super-P and binder PVDF are weighed according to a mass ratio of 90:5:5, mixed to obtain a slurry, coated on an aluminum foil to form a positive electrode material layer, and dried and rolled to obtain a positive electrode sheet.

[0194] Battery:

[0195] The positive electrode sheet, negative electrode sheet and separator prepared above are stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.

[0196] Among them, the negative electrode plate includes negative electrode material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.

[0197] Comparative Example 3

[0198] This comparative example provides a method for preparing a positive electrode material, a positive electrode material, a positive electrode plate, and a battery.

[0199] Preparation method of positive electrode material:

[0200] (1) Preparation of nickel manganese hydroxide precursor Ni 0.25 Mn 0.75 (OH)2:

[0201] S1. Prepare a mixed solution of manganese salt / nickel salt, an ammonia solution and a sodium hydroxide solution with deionized water.

[0202] The molar ratio of manganese salt manganese nitrate to nickel salt nickel nitrate is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 1.5 mol / L, the molar concentration of ammonia water is 2 mol / L; and the molar concentration of sodium hydroxide is 5 mol / L.

[0203] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into a reaction kettle through a peristaltic pump for reaction and aging.

[0204] The reaction temperature was 55°C, the pH of the reaction solution was 10.2, and nitrogen protection was introduced throughout the process.

[0205] S3, centrifuge, wash and dry the aged slurry to obtain Ni 0.25 Mn 0.75 (OH)2.

[0206] (2) Preparation of positive electrode material: The above Ni 0.25 Mn 0.75(OH)2, dopant ZrO2 and lithium source lithium hydroxide are mixed in a mass ratio of 1:0.008:0.238 and then sintered to obtain a positive electrode material.

[0207] The sintering temperature is 750℃, the sintering time is 10h, and Ni 0.25 Mn 0.75 The particle size of (OH)2 is 6 μm, the particle size of ZrO2 is 20 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2 and ZrO2 is 300:1.

[0208] The total time used for the preparation of the positive electrode material is 18 h.

[0209] Cathode Material:

[0210] The positive electrode material is prepared by the above preparation method, and the positive electrode material Li 0.5 Ni 0.5 Mn 1.47 Zr 0.03 O4.

[0211] Positive electrode:

[0212] The positive electrode material, conductive agent Super-P and binder PVDF are weighed according to a mass ratio of 90:5:5, mixed to obtain a slurry, coated on an aluminum foil to form a positive electrode material layer, and dried and rolled to obtain a positive electrode sheet.

[0213] Battery:

[0214] The positive electrode sheet, negative electrode sheet and separator prepared above are stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.

[0215] Among them, the negative electrode plate includes negative electrode material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.

[0216] Comparative Example 4

[0217] This comparative example provides a method for preparing a positive electrode material, a positive electrode material, a positive electrode plate, and a battery.

[0218] Preparation method of positive electrode material:

[0219] (1) Preparation of nickel manganese hydroxide precursor Ni 0.25 Mn 0.75 (OH)2:

[0220] S1. Prepare a mixed solution of manganese salt / nickel salt, an ammonia solution and a sodium hydroxide solution with deionized water.

[0221] The molar ratio of manganese salt manganese nitrate to nickel salt nickel nitrate is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 1.5 mol / L, the molar concentration of ammonia water is 2 mol / L; and the molar concentration of sodium hydroxide is 5 mol / L.

[0222] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into a reaction kettle through a peristaltic pump for reaction and aging.

[0223] The reaction temperature was 55°C, the pH of the reaction solution was 10.2, and nitrogen protection was introduced throughout the process.

[0224] S3, centrifuge, wash and dry the aged slurry to obtain Ni 0.25 Mn 0.75 (OH)2.

[0225] (2) Preparation of positive electrode material: The above Ni 0.25 Mn 0.75 (OH)2 and lithium source lithium hydroxide are mixed in a mass ratio of 1:0.238 and subjected to a primary sintering treatment. The obtained intermediate and coating agent NH4H2PO4 are subjected to a secondary sintering treatment in a mass ratio of 1:0.008 to obtain a positive electrode material.

[0226] The temperature of the first sintering treatment is 750 °C, the time of the first sintering treatment is 10 h, the temperature of the second sintering treatment is 550 °C, and the time of the second sintering treatment is 12 h.

[0227] The total time used for the preparation of the positive electrode material is 30 h.

[0228] Cathode Material:

[0229] The positive electrode material is prepared by the above-mentioned preparation method, and the positive electrode material includes a core part and a coating layer, and the coating layer is coated on at least a part of the surface of the core part. The core part includes Li 0.5 Ni 0.5 Mn 1.5 O4, the coating layer includes Li3PO4, and the thickness of the coating layer is 100nm.

[0230] Positive electrode:

[0231] The positive electrode material, conductive agent Super-P and binder PVDF are weighed according to a mass ratio of 90:5:5, mixed to obtain a slurry, coated on an aluminum foil to form a positive electrode material layer, and dried and rolled to obtain a positive electrode sheet.

[0232] Battery:

[0233] The positive electrode sheet, negative electrode sheet and separator prepared above are stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.

[0234] Among them, the negative electrode plate includes negative electrode material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.

[0235] The batteries of the above-mentioned embodiments and comparative examples were subjected to electrochemical tests, and the test results are shown in Table 1.

[0236] Table 1

[0237]

[0238] As shown in Table 1, by comparing Examples 1 to 7 and Comparative Examples 1 to 4, it can be seen that the present application uses zirconium pyrophosphate as a coating dopant, and simultaneously dopes and coats lithium nickel manganese oxide, which is beneficial to forming a thin coating layer with a high coverage rate on the surface of the lithium nickel manganese oxide, thereby effectively improving the cycle performance of the battery.

[0239] The preparation method of the positive electrode material provided in the present application can achieve Zr ion doping and Li3PO4 coating only by sintering once, which reduces the total preparation time of the positive electrode material and forms a thinner and continuous coating layer, so that the positive electrode material has excellent ion conductivity, reduces the contact area with the electrolyte, reduces side reactions, and improves the capacity retention rate of the battery while ensuring the gram capacity.

[0240] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0241] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. Application of zirconium pyrophosphate as a coating dopant, characterized in that: The zirconium pyrophosphate is mixed with a nickel manganese hydroxide precursor and a lithium source and then subjected to a sintering treatment to obtain a positive electrode material; the positive electrode material includes a core part and a coating layer.

2. The use according to claim 1, characterized in that: The thickness of the coating layer is 2nm~5nm.

3. The use according to claim 1 or 2, characterized in that: The coating rate of the coating layer is greater than 85%.

4. The use according to claim 1 or 2, characterized in that: The general formula of the core is Li a Ni b Mn (8-a-4b-4x) Zr x O4,0 <a<1;0<b<1;0<x<1.5。 5. A method for preparing a positive electrode material, characterized in that: Zirconium pyrophosphate is used as a coating dopant, and the positive electrode material is prepared by the following steps: The zirconium pyrophosphate is mixed with a nickel manganese hydroxide precursor and a lithium source and then sintered to obtain a positive electrode material.

6. The method for preparing the positive electrode material according to claim 5, characterized in that: The sintering temperature is 900°C to 950°C.

7. The method for preparing the positive electrode material according to claim 5, characterized in that: The particle size ratio of the nickel manganese hydroxide precursor to the zirconium pyrophosphate is (100:1) to (500:1); Preferably, the particle size of the nickel manganese hydroxide precursor is 5 μm to 10 μm; Preferably, the particle size of the zirconium pyrophosphate is 20 nm to 50 nm.

8. The method for preparing the positive electrode material according to claim 5, characterized in that: The mass ratio of the nickel manganese hydroxide precursor to the zirconium pyrophosphate is 1:(0.005-0.01).

9. A positive electrode material, characterized in that It is prepared by using zirconium pyrophosphate as a capping dopant.

10. A battery, characterized in that Comprising the positive electrode material according to claim 9.